What explains global exchange rate movements during the financial crisis? - Marcel Fratzscher (European Central Bank (ECB), 2009)
A striking and unexpected feature of the financial crisis has been the sharp appreciation of the US dollar against virtually all currencies globally. The paper finds that negative US-specific macroeconomic shocks during the crisis have triggered a significant strengthening of the US dollar, rather than a weakening. Macroeconomic fundamentals and financial exposure of individual countries are found to have played a key role in the transmission process of US shocks: in particular countries with low FX reserves, weak current account positions and high direct financial exposure vis-à-vis the United States have experienced substantially larger currency depreciations during the crisis overall, and to US shocks in particular.
Keywords: F31; F4; G1; 330; Exchange Rates; financial crisis; global imbalances; shocks; transmission channels; United States; US dollar; Finanzkrise; Wechselkurs; Schock; Außenwirtschaftliches Gleichgewicht; US-Dollar; USA